Pleiotropic tumor suppressive functions of PTEN missense mutations during gliomagenesis - Hyun Jung Jun; Joao A. Paulo; Victoria A. Appleman; Tomer M. Yaron-Barir; Jared L. Johnson; Alan T. Yeo; Vaughn A. Rogers; Shan Kuang; Hemant Varma; Steven P. Gygi; Lloyd C. Trotman; Al Charest (iScience)
Summary: PTEN plays a crucial role in preventing the development of glioblastoma (GBM), a severe and untreatable brain cancer. In GBM, most PTEN deficiencies are missense mutations that have not been thoroughly examined. Here, we leveraged genetically modified mice and isogenic astrocyte cell cultures to investigate the role of clinically relevant mutations (G36E, L42R, C105F, and R173H) in the development of EGFR-driven GBM. We report that the loss of tumor suppression from these mutants is unrelated to their lipid phosphatase activity and rather relate to elevated localization at the cell membrane. Moreover, expression of these PTEN mutations heightened EGFR activity by sequestering EGFR within endomembranes longer and affected its signaling behavior. Through comprehensive studies on global protein phosphorylation and kinase library analyses in cells with the G36E and L42R PTEN mutations, we identified distinct cancer-promoting pathways activated by EGFR, offering targets for treating GBM with these PTEN alterations.